Instructional supervision : applying tools and concepts - Zepeda, Sally J. (New York : Routledge, Taylor & Francis Group, 2017)
This essential text for prospective school leaders enrolled in instructional supervision and evaluation courses provides the knowledge and practical tools to improve teacher effectiveness.
1. Leadership Needed to Promote Supervision, Professional Development, and Teacher Evaluation That Makes a Difference -- 2. Instructional Supervision -- 3. Teacher Evaluation -- 4. Job-Embedded Professional Development -- 5. Instruction and Learning Environments -- 6. Career Stages, Adult Learning, and Supervision -- 7. Motivation and Supervisory Leadership -- 8. Informal and Formal Classroom Observations -- 9. The Pre-observation Conference.
Includes bibliographical references and index.
Keywords: SCHOOL SUPERVISION